2002
DOI: 10.1097/00007691-200212000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Etoposide: Application to Therapeutic Drug Monitoring

Abstract: Antineoplastic agent etoposide (VP16) displays narrow therapeutic index and erratic pharmacokinetics, and dose individualization is a convenient way for overcoming the interpatient variability, so as to maintain the drug exposure within a therapeutic range. The authors proposed a population-based Bayesian methodology to adjust routinely VP16 dosage when given as a 5-day infusion. The mean VP16 pharmacokinetic parameters of the reference population calculated from 14 patients following the two-stage method were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Since only 1 patient out of 23 treated with platinum experienced grade 1 renal toxicity, this increase in CL VP16 cannot be linked to renal dysfunction induced by platinum. Moreover, median CL VP16 in a subgroup of patients treated with platinum (1.89 L/h) was close to values reported in the literature (range, 1.14-2.63 L/h; median, 1.81 L/h) [4,10,15,[30][31][32][33] whilst CL VP16 in the ifosfamide subgroup (median 2.42 L/h) was higher. Thus, it is unlikely that the increase in CL VP16 is due to an interaction between etoposide and platinum compounds, and should rather be imputed to ifosfamide coadministration.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Since only 1 patient out of 23 treated with platinum experienced grade 1 renal toxicity, this increase in CL VP16 cannot be linked to renal dysfunction induced by platinum. Moreover, median CL VP16 in a subgroup of patients treated with platinum (1.89 L/h) was close to values reported in the literature (range, 1.14-2.63 L/h; median, 1.81 L/h) [4,10,15,[30][31][32][33] whilst CL VP16 in the ifosfamide subgroup (median 2.42 L/h) was higher. Thus, it is unlikely that the increase in CL VP16 is due to an interaction between etoposide and platinum compounds, and should rather be imputed to ifosfamide coadministration.…”
Section: Discussionsupporting
confidence: 83%
“…To reach such an aim, it is necessary to determine the expected individual etoposide PK either before or during etoposide administration. Several authors reported studies aimed at monitoring etoposide PK using models and limited sampling strategies [31,43]. Most of them successfully managed to adjust etoposide doses to the target values for steady-state concentrations [31] or for the AUC [15,39,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite its limitations, more and more research is being done on the use of TDM in oncology [73][74][75]. For example, Ratain et al [17] introduced a (complex) formula to dose etoposide based on pretreatment WBC, among others, whereas a populationbased Bayesian methodology to routinely adjust etoposide therapy when given as a 5-day infusion, based on its pharmacokinetic profile as determined on the first day, was proposed by others [76]. In addition, de Jonge et al [77] evaluated the performance and technical feasibility of pharmacokinetically guided dosing of paclitaxel.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…2 demonstrate that the ability of proteasome inhibitors to potentiate Eto-induced cytotoxicity was progressively lost if these compounds are given after the anticancer agent. The limited half-life of Eto (Ciccolini et al, 2002) could contribute to the loss of synergistic activity. The less potent and less selective proteasome inhibitor AllM is faster in losing its activity, which is almost completely abolished after a 4-h delayed exposure, followed by AllN (6 h), and LLnV (7 h).…”
Section: Figmentioning
confidence: 99%